2012
DOI: 10.2337/db11-1367
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cβ Phosphorylates Occludin Regulating Tight Junction Trafficking in Vascular Endothelial Growth Factor–Induced Permeability In Vivo

Abstract: Vascular endothelial growth factor (VEGF)–induced breakdown of the blood-retinal barrier requires protein kinase C (PKC)β activation. However, the molecular mechanisms related to this process remain poorly understood. In this study, the role of occludin phosphorylation and ubiquitination downstream of PKCβ activation in tight junction (TJ) trafficking and endothelial permeability was investigated. Treatment of bovine retinal endothelial cells and intravitreal injection of PKCβ inhibitors as well as expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 42 publications
2
108
0
3
Order By: Relevance
“…19 Similar events were observed recently in vivo during VEGF-induced BRB breakdown. 14 Collectively, these data suggest that the posttranslational modifications to occludin contribute to alterations in tight junction organization and vascular permeability. Others have observed different occludin phosphorylation events associated with BBB permeability.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…19 Similar events were observed recently in vivo during VEGF-induced BRB breakdown. 14 Collectively, these data suggest that the posttranslational modifications to occludin contribute to alterations in tight junction organization and vascular permeability. Others have observed different occludin phosphorylation events associated with BBB permeability.…”
Section: Discussionmentioning
confidence: 91%
“…The cells were treated with 50 ng/mL of human recombinant VEGF (R&D systems, Minneapolis, MN, USA) for 15 minutes, then cells were washed with sterile phosphate-buffered saline twice and harvested in lysis buffer containing protease and phosphatase inhibitors as previously described. 14,29 Western Blotting Immediately after euthanization, retinas were excised, carefully cleaned of all vitreous and retinal pigmented epithelium and then placed in immunoprecipitation buffer (1% Nonidet P-40, 0.25% sodium deoxycholate, 0.1% SDS, 150 mmol/L NaCl, 50 mmol/L Tris (pH 7.5), 2 mmol/L N-ethylmaleimide, 1 mmol/L NaVO4, 10 mmol/L NaF, 10 mmol/L sodium pyrophosphate, 1 mmol/L benzamidine, and complete protease inhibitor cocktail) as previously described. 14 Retinas were gently sonicated followed by 20-minute incubation at 41C and a 10-minute centrifugation at 16,000 g and 41C to sediment insoluble material.…”
Section: Primary Bovine Retinal Endothelial Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, hyperglycemia increases retinal cerebrovascular permeability by activating PKCb. 27,45,46 This robust and widely replicated finding led to initiation of clinical trials to determine whether ruboxistaurin, a related PKCb inhibitor, might treat or delay the progression of diabetic retinopathy in humans. 47 On the other hand, nondiabetic obesity promotes cerebrovascular inflammation, leading to vascular adherence by circulating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin digestion preparation showed that, in addition to pericyte loss, the endothelial cells also disappeared, the so-called acellular capillaries in patients with diabetic retinopathy; 9 experimentally, the intercellular junctions where the tight junction and adherens junction are highly integrated are disrupted in VEGF-treated or diabetic rodents, 10,11 suggesting the diversity of the pathogenesis in BRB breakdown. 12 In addition, histologic studies have reported that cystoid spaces in eyes with macular oedema are the primary structural changes in the retinal parenchyma.…”
Section: Introductionmentioning
confidence: 99%